Breeding success and productivity in the golden eagle (Aquila chrysaetos) in Norway in relation to weather and food availability focusing on the willow ptarmigan (Lagopus lagopus) - Hamar, Hilvi Emerense (Nord universitet, 2024)
Masteroppgave i terrestrisk økologi og naturforvaltning - Nord universitet 2024